Análisis del estilo de comunicación en redes sociales del GAD del cantón Balzar - Macias Cedeño, Riden Yordin (2021)
Social networks are digital platforms formed by communities of individuals with common interests, activities or relationships such as friendship, work relationships, family relationships. Social networks allow contact between people and function as a means to communicate and exchange information. Individuals do not necessarily have to know each other before coming into contact through a social network, but they can do so through it, and that is one of the greatest benefits of virtual communities. These sites facilitate communication between people, the exchange of information (such as photos, videos and more) and allow them to meet new people, further expanding their network. Think about the groups of friends you have, whether they are from college, work, or your family. Each of those groups is a social network that you have. It seems little close to how we see social networks today, doesn't it? Although this premise continues to live within the networks we currently use. Ultimately, the main function of a social network is to connect people within the virtual world, be it to build new social connections or just to maintain existing ones. The success achieved by the social networks we know, such as Facebook and WhatsApp, is undeniable. We can hardly imagine our social interactions without their presence and that shows the strength of these platforms, which take over the world as we know it. Nowadays, social networks have become more necessary for the communication of people, where the GAD of the Balzar canton has used these social networks as a means of communication to the entire canton of events procuring it through social pages, digital media among others media.